Studi Pendahuluan Kualitas Kayu Hutan Tanaman Eucalyptus Pellita F. Muell dengan Teknologi Modifikasi Panas Oil Heat Treatment (OHT) : Preliminary Study of Wood Quality of Plantation Forest of Eucalyptus pellita F. Muell with Oil Heat Treatment Heat Modification Technology - Christy, Eva Oktoberyani; Siska, Grace (HUTAN TROPIKA, 2024)
Indonesia's Industrial Forest Plantations (HTI) cultivate various fast-growing tree species such as Eucalyptus pellita F. Muell. Environmentally friendly and appropriate technologies can be used to improve the weaknesses and deficiencies of wood from HTIs. The Oil Heat Treatment (OHT) process does not use chemicals. This research aims to determine the effect of OHT duration of 0.5 hours, 1.5 hours, and 2.5 hours at a temperature of 200 ± 2°C on the physical properties of Eucalyptus pellita F. Muell. The results showed that the OHT heat treatment using used cooking oil significantly affected the moisture content but did not significantly affect the density